Comparative Study of the Concept of the Welfare State According to Liberal, Islamic and the 1945 Constitution - Abdul Rahman; Akifah Janur, Nur; Ardiansyah (Jurisprudentie : Jurusan Ilmu Hukum Fakultas Syariah dan Hukum, 2022)
This research aims to elaborate the thinking between the concept of the welfare state and the current understanding of democracy in Indonesia. the research used is normative legal research using a conceptual approach. The research results show that the concept of the welfare state emerged as an alternative to constitutional democracy in the 20th century, which was a reaction to the influence of liberal pluralism in the 19th century. This thinking gave rise to the proposition "the least government is the best government". The Welfare State is currently proven to be able to develop the economy while increasing the standard of living of the people. The current crisis of the welfare state, which is often debated, both in Europe and the United States, is not about its existence, but only about its size and capacity. The welfare state is nothing new in Islam. Before being implemented in the West, the Islamic world practiced it first.